Benchmarks in Pancreatic Surgery: A Novel Tool for Unbiased Outcome Comparisons. Issue 2 (August 2019) - Sánchez-Velázquez, Patricia; Muller, Xavier; Malleo, Giuseppe; Park, Joon-Seong; Hwang, Ho-Kyoung; Napoli, Niccolò; Javed, Ammar A.; Inoue, Yosuke; Beghdadi, Nassiba; Kalisvaart, Marit; Vigia, Emanuel; Walsh, Carrie D.; et al.
Abstract : Objective: To use the concept of benchmarking to establish robust and standardized outcome references after pancreatico-duodenectomy (PD). Background: Best achievable results after PD are unknown. Consequently, outcome comparisons among different cohorts, centers or with novel surgical techniques remain speculative. Methods: This multicenter study analyzes consecutive patients (2012–2015) undergoing PD in 23 international expert centers in pancreas surgery. Outcomes in patients without significant comorbidities and major vascular resection (benchmark cases) were analyzed to establish 20 outcome benchmarks for PD. These benchmarks were tested in a cohort with a poorer preoperative physical status (ASA class ≥3) and a cohort treated by minimally invasive approaches. Results: Two thousand three hundred seventy-five (38%) low-risk cases out of a total of 6186 PDs were analyzed, disclosing low in-hospital mortality (⩽1.6%) but high morbidity, with a 73% benchmark morbidity rate cumulated within 6 months following surgery. Benchmark cutoffs for pancreatic fistulas (B-C), severe complications (≥ grade 3), and failure-to-rescue rate were 19%, 30%, and 9%, respectively. The ASA ≥3 cohort showed comparable morbidity but a higher in hospital-mortality (3% vs 1.6%) and failure-to-rescue rate (16% vs 9%) than the benchmarks. The proportion of benchmark cases performed varied greatly across centers and continents for both open (9%–93%) and minimally invasive (11%–62%) PD. Centers operating mostly on complex PD cases disclosed better results than those with a majority of low-risk cases. Conclusion: The proposed outcome benchmarks for PD, established in a large-scale international patient cohort and tested in 2 different cohorts, may allow for meaningful comparisons between different patient cohorts, centers, countries, and surgical techniques. Abstract : Supplemental Digital Content is available in the text